2021
DOI: 10.3390/cancers13071591
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Screens in Synthetic Lethality and Combinatorial Therapies for Cancer

Abstract: Cancer is a complex disease resulting from the accumulation of genetic dysfunctions. Tumor heterogeneity causes the molecular variety that divergently controls responses to chemotherapy, leading to the recurrent problem of cancer reappearance. For many decades, efforts have focused on identifying essential tumoral genes and cancer driver mutations. More recently, prompted by the clinical success of the synthetic lethality (SL)-based therapy of the PARP inhibitors in homologous recombinant deficient tumors, sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 178 publications
(150 reference statements)
0
24
0
Order By: Relevance
“…In this article, we present a small snapshot of the utility of gene editing tools that can be brought to bear to further our knowledge of two DNA repair pathways, MMR and BER. The far-reaching implications of CRISPRbased gene editing go well beyond basic science research with roles in medicine and therapeutics [423], gene therapy [424], agriculture [425], advances in animal modeling [426], and cancer discovery [427]. CRISPR methods open the door to the personalized treatment of genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we present a small snapshot of the utility of gene editing tools that can be brought to bear to further our knowledge of two DNA repair pathways, MMR and BER. The far-reaching implications of CRISPRbased gene editing go well beyond basic science research with roles in medicine and therapeutics [423], gene therapy [424], agriculture [425], advances in animal modeling [426], and cancer discovery [427]. CRISPR methods open the door to the personalized treatment of genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have confirmed that CRISPR-based screens have improved reproducibility compared to RNAi screening approaches, likely due to the lower off-target frequency of gRNAs and the higher efficiency of CRISPR reagents from creating knockout mutants rather than RNA-targeted knockdowns [ 112 , 113 , 114 ]. Thus, large-scale CRISPR/Cas9 screens have proven to be a powerful method identifying genetic defects in tumors harboring oncogenic mutations such as KRAS [ 115 , 116 ]. Table 2 summarizes a selection of the most relevant CRISPR/Cas9 screens carried out to date, focusing on a few illustrative examples below.…”
Section: Screening Approaches To Identify Synthetic Lethal Interactio...mentioning
confidence: 99%
“…During the last several years, the use of biocomputational methods in combination with CRISPR/Cas9 knockout screens has become a highly powerful technique to elucidate essential cancer genes and define important therapeutic targets [ 116 , 140 , 141 , 142 ]. Although many studies have enumerated interesting KRAS synthetic lethal targets, these findings are not applicable to all KRAS -mutant cancer contexts because of the heterogeneity associated to this oncogenic mutation.…”
Section: The Future Of the Search For Synthetic Lethal Interactors Fo...mentioning
confidence: 99%
“…Cancer heterogeneity presents major challenges for the development of personalized treatments [ 1 , 2 , 3 , 4 ]. Current precision therapies used in the treatment of cancer are designed to exploit a variety of different biological entities characteristic to individual cancer types, such as activated protein kinases, estrogen receptor, and defective DNA repair enzymes [ 4 , 5 , 6 ]. Understanding the mechanistic details of cancer biology is critical for improving diagnostic tools and for developing new therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%